Localizing Antifungal Drugs to the Correct Organelle Can Markedly Enhance their Efficacy. (2nd May 2018) - Benhamou, Raphael I.; Bibi, Maayan; Berman, Judith; Fridman, Micha
Abstract: A critical aspect of drug design is optimal target inhibition by specifically delivering the drug molecule not only to the target tissue or cell but also to its therapeutically active site within the cell. This study demonstrates, as a proof of principle, that drug efficacy can be increased considerably by a structural modification that targets it to the relevant organelle. Specifically, by varying the fluorescent dye segment an antifungal azole was directed from the fungal cell mitochondria to the endoplasmic reticulum (ER), the organelle that harbors the drug target. The ER‐localized azole displayed up to two orders of magnitude improved antifungal activity and also dramatically reduced the growth of drug‐tolerant fungal subpopulations in a panel of Candida species, which are the most prevalent causes of serious human fungal infections. The principle underlying the "target organelle localization" approach provides a new paradigm to improve drug potency and replenish the limited pipeline of antifungal drugs. Abstract : Der Transport antimykotischer Azol‐basierter Wirkstoffe zum endoplasmatischen Retikulum – der Organelle, in der sich ihr Zielenzym befindet – führte zu verbesserter Aktivität gegen Candida ‐Spezies (den häufigsten Verursacher ernsthafter Pilzinfektionen des Menschen) und unterdrückte das Wachstum Wirkstoff‐toleranter Pilz‐Subpopulationen.